การสื่อสารเพื่อการเปลี่ยนแปลงองค์กร - Doherty, Wanawan (Asian Health, Science and Technology Reports, 2012)
ทุกวันนี้องค์กรส่วนใหญ่จำเป็นต้องมีการจัดการการเปลี่ยนแปลงองค์กรอันเนื่องมาจากปัจจัยทั้งภายในและภายนอกที่องค์กรไม่สามารถจะหลีกเลี่ยงได้ เพื่อที่จะสามารถยืนหยัดในท่ามกลางภาวะการแข่งขันที่เข้มข้น ตลอดจนสามารถที่จะนำพาองค์กรอยู่รอดและมีความก้าวหน้าต่อไปได้ และการที่จะดำเนินการปลี่ยนแปลงองค์กรนั้นผู้บริหารต้องให้ความสำคัญกับการใช้การสื่อสารในองค์กรควบคู่ไปกับการบริหารจัดการอื่นๆ เนื่องจากการสื่อสารในองค์กรเป็นการแลกเปลี่ยนข่าวสาร ความคิดและทัศนคติของกลุ่มบุคคลในองค์กรที่มีความสัมพันธ์กันแต่มีความเชี่ยวชาญการปฏิบัติงานในหน้าที่ที่แตกต่างกัน โดยมีการใช้เทคโนโลยีสื่อสารเพื่อแลกเปลี่ยนข่าวสารนั้น ทั้งนี้ก็เพื่อดำเนินกิจกรรมต่างๆ ให้บรรลุวัตถุประสงค์ที่ตั้งไว้ ผู้เขียนจึงได้นำเสนอแบบจำลองการสื่อสารเพื่อการเปลี่ยนแปลงองค์กรสำหรับการเผยแพร่ความรู้ความเข้าใจเกี่ยวกับการเปลี่ยนแปลงองค์กรให้กับบุคลากร โดยผ่านกระบวนการ 5 ขั้นตอน ขั้นตอนที่หนึ่งเป็นการสื่อสารเพื่อสร้างการรับรู้ (knowledge) เกี่ยวกับการเปลี่ยนแปลงในองค์กรว่าจะมีการดำเนินการเปลี่ยนแปลงองค์กรให้บุคลากรทุกคนได้รับทราบ ขั้นที่สองเป็นการสื่อสารเพื่อโน้มน้าวใจ (persuasion) เพื่อกระตุ้นให้บุคลากรในองค์กรเกิดความร่วมมือในอันที่จะร่วมดำเนินการเปลี่ยนแปลงองค์กร ขั้นที่สามเป็นการสื่อสารภายในองค์กรที่จะให้ข้อมูลเพิ่มเติมเพื่อให้เกิดการตัดสินใจ (decision) ในการร่วมมือกันเพื่อการเปลี่ยนแปลงองค์กร ขั้นตอนที่สี่เป็นการสื่อสารเพื่อกระตุ้นให้เกิดการนำการเปลี่ยนแปลงนั้นมาใช้ (implementation) ในองค์กรร่วมกัน และขั้นตอนสุดท้ายเป็นการสื่อสารเพื่อการยืนยัน (confirmation) โดยการย้ำเตือนข่าวสารในทางบวกด้านความสำเร็จเกี่ยวกับการเปลี่ยนแปลงองค์กรเพื่อที่จะสร้างความเชื่อมั่นให้กับบุคลากรเพื่อร่วมดำเนินการต่อไป ทั้งนี้การสื่อสารภายในองค์กรนั้นจะต้องมีการเผยแพร่ผ่านสื่อต่างๆ ที่เหมาะสม โดยเฉพาะการใช้สื่อใหม่ที่ได้รับความนิยมเพิ่มขึ้นโดยลำดับ ทั้งหมดนี้ก็เพื่อสร้างบรรยากาศของการเปลี่ยนแปลงให้เกิดขึ้นในองค์กรที่นำไปสู่ทัศนคติหรือความรู้สึกทางบวกจนนำไปสู่ความเชื่อใจ ความมั่นคงในหน้าที่การงาน และความมีอำนาจในการที่จะจัดการกับการเปลี่ยนแปลงนั้น และพร้อมที่จะเปลี่ยนแปลงไปสู่การเป็นองค์กรที่มีการเปลี่ยนแปลงอย่างมีประสิทธิภาพและประสิทธิผล และประสบความสำเร็จตามเป้าหมายที่องค์กรต้องการได้ แต่หากองค์กรไม่ได้นำการสื่อสารในองค์กรเข้ามาเพื่อสร้างความรู้ความเข้าใจกับสิ่งที่องค์กรจะดำเนินการเปลี่ยนแปลงสู่บุคลากรในองค์กรหรือสร้างบรรยากาศของการเปลี่ยนแปลงในองค์กรอย่างพอเพียงแล้ว อาจทำให้เกิดทัศนคติหรือความรู้สึกทางลบ เกิดความกลัว ไม่เชื่อใจ รู้สึกไม่มั่นคง กังวลใจและการจะสูญเสียอำนาจ จนเกิดการต่อต้านการเปลี่ยนแปลงซึ่งนำไปสู่ความล้มเหลวในการเปลี่ยนแปลงองค์กรและอาจทำให้องค์กรถดถอยหรือไม่ประสบความสำเร็จตามที่ต้องการได้ Nowadays many organizations are faced with the needs to implement corporate changes due to inevitable factors, both internal and external, in order to survive in the increasingly competitive environments as well as to progress and keep pace with the advancing world. The implementation of changes within an organization requires that the executives pay attention to the use of organizational/ internal communication in tandem with other means of administration and management. Communication in organization facilitates, through Information Technology, the exchange of news, viewpoints and attitudes of different groups of corporate personnel who are professionally related yet possessing different kinds of expertise to conduct activities that will lead to the attainment of the corporate goals. Since organizational changes are no longer to be avoided, effective organizational/internal communication regarding the changes is essential. The researcher, therefore, proposes a model for organizational/internal communication of corporate changes to inform the corporate personnel of any readjustment so that they share the knowledge and understanding of the changes. The proposed model features five communicative steps. Step One is Communication for Knowledge: to inform the personnel of the coming changes in the corporate operation. Step Two is Communication for Persuasion: to encourage the personnel to cooperate in the corporate changes. Step Three is Communication for Decision: to provide additional information to facilitate the personnel’s decision to contribute to the corporate changes. Step Four is Communication for Implementation: to promote the implementation of the changes among the corporate personnel. Lastly, Step Five is Communication for Confirmation: to remind the personnel of positive news of the corporate changes to gain their trust and willingness for further cooperation. Communication in organization, in addition, should be conveyed through appropriate media, especially through certain new media that are becoming ever more popular, to generate the atmosphere of change within the organization. This will lead to positive attitudes and feelings, and eventually to trust, job security, the power to manage change, the readiness to transform into an organization of efficient and effective change, and the achievement of corporate goals. On the other hand, if communication in organization is ignored or not sufficiently implemented in the context of internal change, the results could be unpleasant: negative attitudes and feelings, fear, distrust, sense of insecurity, and worries of losing control of power. This might lead to the resistance of change and eventually to the failure to implement changes in the organization. The end result would be a deteriorating organization with unfulfilled goals.